2019
DOI: 10.1007/s00408-019-00227-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Long-Term Follow-Up of Patients with Life-Threatening, Inhaled Synthetic Cannabinoids-Associated Coagulopathy in Chicago

Abstract: A large-scale outbreak of life-threatening, inhaled synthetic cannabinoids (Spice/K2)-associated coagulopathy with bleeding complications was recently reported in Illinois. The causative agents were brodifacoum, difenacoum and bromadiolone, potent, long-acting, 4-hydroxycoumarin anticoagulant rodenticides (LAAR), that were mixed with Spice/K2 products procured and then inhaled by the victims. We report on 3 poisoned patients who reside in underserved, socioeconomically-disadvantaged neighborhoods of Chicago th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…To that end, the qualitative LC-MS/MS LAARs assay offered by NMS Labs [13] to treating physicians during the outbreak in Illinois can detect only brodifacoum in blood samples and is inefficient for monitoring poisoned patients over time as several tests would have been required until blood concentrations dropped to <10 ng/mL, the detection level of the assay [4][5][6]12,13]. By contrast, our rapid (<15 min), highly-sensitive, quantitative, and validated LC-MS/ MS assay can provide critical information to guide patient care during and after hospitalization, including identification of several offending LAARs, estimates of the ingested dose, and dosage and discontinuation of oral vitamin K 1 therapy after hospital discharge once plasma LAARs concentrations decreased to a safe level (<10 ng/mL) [6,9,10,[14][15][16]. Treating physicians will request quantitative plasma LAARs testing, report test results in the patient's hospital discharge summary, and recommend regular monitoring of plasma LAARs concentrations in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To that end, the qualitative LC-MS/MS LAARs assay offered by NMS Labs [13] to treating physicians during the outbreak in Illinois can detect only brodifacoum in blood samples and is inefficient for monitoring poisoned patients over time as several tests would have been required until blood concentrations dropped to <10 ng/mL, the detection level of the assay [4][5][6]12,13]. By contrast, our rapid (<15 min), highly-sensitive, quantitative, and validated LC-MS/ MS assay can provide critical information to guide patient care during and after hospitalization, including identification of several offending LAARs, estimates of the ingested dose, and dosage and discontinuation of oral vitamin K 1 therapy after hospital discharge once plasma LAARs concentrations decreased to a safe level (<10 ng/mL) [6,9,10,[14][15][16]. Treating physicians will request quantitative plasma LAARs testing, report test results in the patient's hospital discharge summary, and recommend regular monitoring of plasma LAARs concentrations in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we propose that this highly-sensitive quantitative assay for plasma LAARs should be available to physicians treating patients with acute LAARs poisoning because it can provide critical information to guide patient care during and after hospitalization, including identification of the offending LAARs, estimates of the ingested dose, and assistance in determining dose and treatment duration of oral vitamin K 1 after hospital discharge [8]. To that end, premature discontinuation of oral vitamin K 1 during follow-up when coagulation studies are within the normal range may result in recurrence of coagulopathy, bleeding, and death [9,10]. Regular monitoring of plasma LAARs concentrations until a safe level (<10 ng/mL) is reached could then mitigate this ominous clinical scenario [4][5][6].…”
Section: The Clinical Challengementioning
confidence: 99%
“…An outbreak of SC-associated coagulopathy reported in Illinois showed that the causative agents were brodifacoum, difenacoum, and bromadiolone, which are potent, long-acting anticoagulant rodenticides (LAAR) [ 12 ]. But brodifacoum is by far the biggest culprit in SC-associated coagulopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory complications in inhaled or vaporized forms as rhinitis, chronic bronchitis, and pulmonary hemorrhage and coagulopathy in synthetic presentations of inhaled cannabinoids are described 129,130 . Local injury in oromucosal after prolonged use of THC/CBD oromucosal spray is referred by some MS patients.…”
Section: Safety In Using Cannabis-based Treatmentmentioning
confidence: 99%